Toward a sustainable post-pandemic growth - Ivan Sudibyo (Priviet Social Sciences Journal, 2026)
This study investigates the long-run relationship between Research and Development (R&D) expenditure, Foreign Direct Investment (FDI) inflows, financial market capitalization, population, and Carbon Dioxide (CO2) emissions across five ASEAN economies–Indonesia, Malaysia, Singapore, Thailand, and Vietnam–over 2000–2023. Building on the Paramati et al. (2021) framework rooted in the Impact, Population, Affluence, Technology (IPAT) theory of Ehrlich and Holdren (1971), the study applies Pedroni's panel cointegration test, the Pesaran (2007) CIPS unit-root test to address cross-sectional dependence, and Fully Modified OLS (FMOLS) estimation at both the panel and country-level. Results show that (i) population is the most consistently significant driver of CO2 emissions across all five economies, (ii) R&D expenditure carries a negative but statistically insignificant coefficient, a result consistent with the region's structurally low R&D-to-Gross Domestic Product (GDP) ratios and lagged green-technology effects (Yang et al., 2025; Mehmood et al., 2022), and (iii) FDI and financial-market effects are heterogeneous, supporting a Malaysia-Singapore green-finance interpretation alongside pollution-haven dynamics elsewhere. The findings highlight the need for ASEAN policymakers to scale R&D intensity, channel financial market deepening toward green sectors, and integrate demographic-driven emission pressures into national climate plans.